دراسة المصل الناتج أثناء صناعة بعض أنواع الجبن المحلي لاستخدامه في صناعة بعض أنواع المشروبات المرطبة - سلطانه علي; محمد أحمد; صقور سماهر (Latakia University Journal -Biological Sciences Series, 2013)
تناول هذا البحث إمكانية الاستفادة من مصل الجبن في إنتاج مشروبات مرطبة مدعمة بعصائر طبيعية (دراق, برتقال, تفاح, رمان ). وقد تم الحصول على المصل مخبرياﹰ بنوعيه (الحلو والحامضي), وتحديد أهم الخواص الحسية والكيميائية للمصل الناتج, حيث كانت نسبة المواد الصلبة الكلية واللاكتوز في المصل الحلو 6.2 ± 0.2, 4.5 ± 0.2 على التوالي, أما في المصل الحامضي فكانت نسبة المواد الصلبة واللاكتوز 5.4 ± 0.2, 3.8 ± 0.2 على التوالي. أثبت التقييم الحسي للمصل الحلو الطازج قابلية متوسطة للاستهلاك, بينما كان المصل الحامضي غير مقبول لدى فريق المحكمين عند مستوى معنوية 5%. وبين التقييم الحسي أن أفضل نسب الخلط كانت 50 – 50 حجماً للمصل والعصير, حيث كانت درجة القبول جيدة جداﹰ. وقد تفوق المشروب المصنع من عصير البرتقال على الأنواع الأخرى عند مستوى معنوية 5%, وجاء بعده المشروب المصنع من عصائر الرمان, التفاح, الدراق على التوالي. وبالنتيجة يمكن استخدام المصل الحلو بعد خلطه بأحد العصائر المدروسة بنسبة تزيد عن 40 %, والمثلى 50 %, لإنتاج مشروب مرطب جيد يجب استهلاكه خلال 24 ساعة على الأكثر بسبب انخفاض قابليته للتخزين, نظراﹰ لخلوه من المواد الحافظة وعدم تعريضه لأي معاملة حرارية, ويحتاج تحسين هذه القابلية إلى إجراء المزيد من الدراسات. This research investigates the ability of using cheese whey in producing soft drinks supported with natural juices (peach, orange, apple, and pomegranate). Two kinds of whey (sweet and sour) were prepared in the laboratory, and their most important organoleptic and chemical properties were determined. The percentages of total solids and lactose in sweet whey were 6.2 ±0.2% and 4.5 ±0.2% respectively, while for sour whey were 5.4 ±0.2% and 3.8 ±0.2%. Organoleptic evaluation showed that the fresh sweet whey had medium ability for consumption, while sour whey was rejected by the team of tasters with a significance level of 5%. Organoleptic evaluation also showed that the best percentage for the mixture of sweet whey and juice is 50:50 (v/v) with a very good degree of acceptance. Statistical analysis indicated that the produced drink from orange juice was the best drink at 5% significance level. It was followed by the juices of pomegranate, apple and peach respectively. As a result the sweet whey may be used after mixing it with the other studied juices at a percentage exceeding 40%, (best value is 50%) for the production of good soft drink. This produced drink must be consumed within a maximum period of 24 hours because of its low storability due to the absence of preservatives and heat treatment. Improving this storability requires further studies.